“Enhancing Professional Competencies of Physical Education Teachers in Higher Education through Interactive and Digital Learning Technologies” - Musayev Otabek Qudratovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the enhancement of professional competencies of physical education teachers in higher education through the use of interactive and digital learning technologies. The study focuses on the integration of theoretical knowledge, practical skills, and pedagogical reflection to develop teachers’ professional potential. It highlights the effectiveness of interactive lessons, online platforms, and modern teaching tools in improving lesson quality, student engagement, and holistic development. The article also examines strategies for implementing competency-based approaches and technological innovations in physical education instruction.